In vitro fermentation parameters and biohydrogenation of vegetable oils without glycerol - Castagnino, Pablo de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Glycerol combined with vegetable oils could limit biohydrogenation and enhance the reduction in methane production without depressing digestibility and microbial population. Three in vitro incubations were conducted to evaluate the effect of glycerol (0 or 150 g/kg DM) combined with three different diets: Tifton 85 hay without oil seeds (HWO), Tifton 85 hay + 80g of soybean oil/kg DM (HSO) and Tifton 85 hay + 80 g of linseed oil/kg DM (HLO) incubated for 0, 6, 12 and 24 h on fatty acid composition and ruminal fermentation parameters. Real-time PCR was used to quantify microbial population at 24 h. Methanogens, fibrolitic and lipolityc bacteria were expressed as a proportion of total rumen bacterial 16 S rDNA. Separately, kinetic of gas production was assessed at 2, 4, 6, 8, 10, 12, 14, 18, 22, 24, 36, 42 and 48 h. In vitro true digestibility (IVTD) and CH4 (%/g DMD) production were evaluated at 48 h. The experimental design for fatty acid composition and ruminal parameters was a randomized block in a factorial arrangement 2 x 3 x 4, involving the following factors: glycerol (2), diets (3) and time (4). Microbial quantification, IVTD and CH4 were evaluated with the same design but without time as a factor. The pH value and ammonia (NH3-N) concentration were lower in HWO compared with HSO and HLO diets, regardless of glycerol addition (P<0.05). Anaerovibrio lipolytica proportion increased 84, 33 and 13 times in HWO, HSO and HLO diets with glycerol, respectively, compared with diets without glycerol (P<0.05). Ruminococcus albus, Ruminococcus flavefaciens and Butyrivrio VA and SA subgroup did not change with glycerol and oil addition (P>0.05). Among all cellulolytic bacteria, Fibrobacter succinogenes was the most sensitive to the addition of vegetable oil in the diet (P<0.05). CH4 production decreased in HSO diet associated with glycerol and HLO diets with or without glycerol addition (P<0.05). Lag time decreased in HWO and HSO diets ...

O glicerol combinado com óleos vegetais poderia limitar a intensa biohidrogenação dos ácidos graxos de cadeia longa e a produção de metano sem causar efeitos deletérios sobre a população microbiana e digestibilidade. Três incubações in vitro foram conduzidas para avaliar o efeito do glicerol (0 or 150 g/kg MS) combinado com três diferentes dietas: Feno de Tifton 85 sem a inclusão de óleo (FSO), Feno de Tifton 85 + 80g de óleo de soja/kg MS (FOS) e Feno de Tifton 85 + 80 g de óleo de linhaça/kg MS (FOL) incubados por 0, 6, 12 e 24 h sobre a composição de ácidos graxos e os parâmetros de fermentação ruminal. A PCR em tempo-real (qPCR) foi utilizado para quantificação de microorganismos às 24 h. As arquéias metanogênicas ,bactérias celulolíticas e lipolíticas foram expressas em função das bactérias totais. Separadamente, a cinética de produção de gases foi avaliada nos tempos 2, 4, 6, 8, 10, 12, 14, 18, 22, 24, 36, 42 e 48 h. A digestibilidade verdadeira in vitro (DVIV) e a produção CH4 (%/g DMS) foram avaliadas às 48 h. Os valores de pH e as concentrações de amônia (NH3-N) foram menores nas dietas FSO comparado com FOS e FOL, independente da adição de glicerol (P<0,05). A proporção da Anaerovibrio lipolytica aumentou 84, 33 e 13 vezes nas dietas FSO, FOS e FOL com adição de glicerol, respectivamente, comparadas com as dietas sem glicerol (P<0,05). Ruminococcus albus, Ruminococcus flavefaciens e os subgrupos Butyrivrio VA e SA subgroup não foram alteradas com a inclusão dos óleos vegetais e de glicerol (P>0,05). As bactérias Fibrobacter succinogenes foram mais sensíveis a adição de óleos vegetais entre todas as bactérias celulolíticas (P<0,05). A DVIV e a produção de CH4 foram inferiores nas dietas FOS com adição de glicerol e na dieta FOL independente da adição de glicerol (P<0,05). A redução na produção de gases ocorreu nas dietas FOS e FOL associadas com glicerol ...
Keywords: Metano; Glicerina; Bacterias; Oleos e gorduras; Oleo de soja; Methane